2006
DOI: 10.1021/ja061654w
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Templating of Surfaces:  Adsorption of (S)-2-Methylbutanoic Acid on Pt(111) Single-Crystal Surfaces

Abstract: The adsorption and thermal chemistry of (S)-(+)-2-methylbutanoic acid ((S)-2MBA) on Pt(111) single-crystal surfaces was characterized by using temperature programmed desorption (TPD) and reflection-adsorption infrared (RAIRS) spectroscopies. Particular emphasis was placed on the characterization of the chiral superstructures formed upon the deposition of the submonolayer coverages of enantiopure (S)-2-methylbutanoate species that are produced by thermal dehydrogenation of the (S)-2MBA. The enantioselectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 47 publications
4
88
1
Order By: Relevance
“…Instead, it is hypothesized that the adsorbed MBA molecules form supramolecular structures with a long-range order. 25 This overlayer can be considered as a proxy for a templating-type of chirality induction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it is hypothesized that the adsorbed MBA molecules form supramolecular structures with a long-range order. 25 This overlayer can be considered as a proxy for a templating-type of chirality induction.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, both chirally-modified surfaces were previously reported to exhibit appreciable enantioselectivity in the adsorption of PO enantiomers, both in terms of the adsorption energies and of the amount of the adsorbed PO. 25,26 To verify these findings and to obtain accurate adsorption energies using a direct calorimetric measurement, we measured the PO adsorption energies as a detailed function of the PO coverage at a constant modifier coverage. Complementarily, we varied the surface coverages of the chiral modifiers to tune the properties of the chiral surface overlayers and determined the PO adsorption energies on these surfaces.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the arena of chiral assembly, tartaric acid [2][3][4][5][6][7][8][9][10], cinchona alkaloids [11][12][13] and heptahelicene [14][15][16] are among the most commonly studied molecules. Several reports in the literature have revealed that chiral adlayers on achiral surfaces exhibit enantiospecific interactions with chiral probe molecules [17][18][19][20]. For example, (S)-propylene oxide exhibits a preference for adsorption on a Pt(111) surface modified with (S)-butoxide over an identical surface modified with (R)-butoxide, with the former system adsorbing 35% more of the probe molecule than the latter [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, chiral heterogeneous catalysis has received special attention as a convenient technique for the manufacture of enantiomerically pure compounds (Lee and Zaera 2006). One promising route for achieving this is to use chiral modifiers to endow enantioselective properties onto a metallic surface (Baiker and Blaser 1997).…”
Section: Introductionmentioning
confidence: 99%